Intestinal helminths in wild Peruvian red uakari monkeys (Cacajao calvus ucayalii) in the northeastern Peruvian Amazon. Issue 2 (13th December 2013) - Conga, David F.; Bowler, Mark; Tantalean, Manuel; Montes, Daniel; Serra‐Freire, Nicolau Maués; Mayor, Pedro
Abstract Parasites are important in the management of the health of primate populations. We examined 36 fecal samples from Peruvian red uakari monkeys (Cacajao calvus ucayalii) collected from wild animals in the northeastern Peruvian Amazon. Samples were positive for helminth infection. Nematodes egg: Strongyloididae, Trypanoxyuris sp., Spirurid, and a cestode egg were identified.